A genome-wide assessment of genetic diversity and population structure of Korean native cattle breeds. Issue 1 (December 2016) - Sharma, Aditi; Lee, Seung-Hwan; Lim, Dajeong; Chai, Han-Ha; Choi, Bong-Hwan; Cho, Yongmin
Abstract Background The native cattle breeds are an important genetic resource for meat and milk production throughout Asia. In Asia cattle were domesticated around 10, 000 years ago and in Korea cattle are being raised since 2000 B.C. There are three native breeds of cattle in Korea viz. Brown Hanwoo, Brindle Hanwoo and Jeju Black. While one of these breeds, Brown Hanwoo, is a part of a Food and Agricultural Organization and national genetic evaluation plans, others get little attention. This study is an effort to understand and provide a detailed insight into the population structure and genetic variability of the Korean cattle breeds along with other Asian breeds using various methods. In this study we report the genetic variation and structure of the Korean cattle breeds and their comparison with five other Asian cattle breeds along with a panel of animals from Europeantaurine, Africantaurine andindicine cattle breeds. Results Asian cattle were found to be least differentiated which reflects their recent history. Amongst the Asian breeds Hainan, which is anindicine breed, had the lowest gene diversity while Yanbian had the highest followed by Mongolian and Korean cattle. Amongst the Korean breeds Brown Hanwoo had the highest diversity followed by Brindle Hanwoo and Jeju Black. The genetic diversity in Asian cattle breeds was found to be comparable to the Europeantaurines and more than the Africantaurine s andZebu cattle. Korean cattle breed, Brown Hanwoo was consistently found to be closer to Yanbian, a Chinese cattle breed. We found low divergence and moderate levels of genetic diversity among the native Korean breeds. Indicine introgression from Hainan was seen in other Asian breeds. From Europe, Limousin, Holstein and Hereford introgression was found in Asian breeds. Conclusions In this study we provide a genome-wide insight into the genetic history of the native cattle breeds of Korea. The outcomes of this study will help in prioritization and designing of the conservation plans.